PEMIKIRAN K.H. AHMAD DAHLAN TENTANG PENDIDIKAN DAN IMPLEMENTASINYA DI SMP MUHAMMADIYAH 6 YOGYAKARTA TAHUN 2014/2015 - Ahmad, Fandi (Profetika, 2015)
The objective of this research is to describes K.H. Ahmad Dahlanâs thought of Muhammadiyah education and related to evaluating implementation about K.H. Ahmad Dahlans thought in SMP Muhammadiyah 6 Yogyakarta. The concept of Muhammadiyah education whose pioneered by K.H. Ahmad Dahlan apply holistic education. The education which combines general and religious education in the curriculum. This education will generate student who not only excellent in general knowledge but also in religious knowledge. By means of this research, researchers wanted to knowing the concept of Muhammadiyah education and that implementation in SMP Muhammadiyah 6 Yogyakarta. The data collected though interview to information resources, observation, and documentation study will be analyzed by qualitatively and descriptive served. Based on the results of descriptive analyzed revealed that the K.H. Ahmad Dahlanâs thought of Muhammadiyah education denote combines general education with religious education into a single unit are inseparable from one each other. Hence, this concept of Muhammadiyah education whose pioneered by K.H. Ahmad Dahlan not yet implementation in SMP Muhammadiyah 6 Yogyakarta because of the teachers still understand about the concept of Muhammadiyah education.Keywords: education; implementation; Â MuhammadiyahÂ